2022
DOI: 10.1186/s40942-021-00353-1
|View full text |Cite
|
Sign up to set email alerts
|

Birdshot retinochoroiditis in Brazil: a multicenter review of 40 patients

Abstract: Background Birdshot retinochoroiditis (BRC) is a rare and chronic bilateral uveitis mostly found in Caucasians. As few data are available about the clinical course of BRC in Hispanic patients, we aimed to report the clinical findings and the evolution of BRC in Brazilian patients. Methods This retrospective cohort multicenter nationwide study was performed by analyzing the records of patients with BRC diagnoses from Brazilian ophthalmological cente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 33 publications
0
5
1
Order By: Relevance
“…Contrary to what has been found by several recent study [ 27 , 28 ], we found a statistically significant improvement in BCVA before/after treatment, overall and in the two groups of interest. It should be noted, however, that although the mean initial BCVA did not differ between these two groups, there was a different distribution of patients between subgroups: our results suggest a greater visual improvement for patients with severely impaired initial BCVA (<20/40 Snellen, Log MAR 0.30) in the methylprednisolone group, supporting our practice of administering corticosteroids loading doses to these patients.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to what has been found by several recent study [ 27 , 28 ], we found a statistically significant improvement in BCVA before/after treatment, overall and in the two groups of interest. It should be noted, however, that although the mean initial BCVA did not differ between these two groups, there was a different distribution of patients between subgroups: our results suggest a greater visual improvement for patients with severely impaired initial BCVA (<20/40 Snellen, Log MAR 0.30) in the methylprednisolone group, supporting our practice of administering corticosteroids loading doses to these patients.…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, nearly a fifth of patients were experiencing a relapse or had not reach control at the end of follow up. In our experience and as demonstrated in many studies [ 31 , 33 ], BSCR is a condition requiring prolonged treatment with a very slow tapering in corticosteroid therapy, sometimes with the long-term maintenance of a low dose of cortisone if well tolerated (>30 months according to Maleki et al [ 28 ]). As relapses occurred in nearly a third of patients per year, a delay of three months does not allow us to consider a patient in remission, thereby explaining the major difference in results between the study issued by Crowell et al and ours.…”
Section: Discussionmentioning
confidence: 81%
“…Descrita inicialmente por Ryan e Maumenee em 1980, a coriorretinopatia de Birdshot (BCR) é uma uveíte posterior crônica, não infecciosa, bilateral, caracterizada por múltiplos pontos hipopigmentados coroidianos. (1)(2)(3) É uma doença rara, que acomete de 0,1 a 0,6 indivíduo para cada 100 mil habitantes, predominando em mulheres de meia-idade (média de 50 anos), caucasianas e com forte associação ao HLA-A29 (90 a 95% dos pacientes com BCR são positivos). (2,4) O paciente pode queixar-se de moscas volantes, fotopsias, visão borrada, perda de campo visual periférico, discromatopsia e nictalopia, muitas vezes com acuidade visual (AV) de 1,0.…”
Section: Introductionunclassified
“…(4) Na angiofluoresceinografia (AFG), as lesões são hipofluorescentes, mas podem ser hiperfluorescentes em estágios crônicos (por defeito em janela). (1) Geralmente, não são bem delimitadas, sendo mais definidas com a indocianina verde (ICV) como lesões focais hipofluorescentes. O exame de tomografia de coerência óptica (OCT) é capaz de demonstrar as lesões coroidianas, além de edema macular e alteração na zona elipsoide.…”
Section: Introductionunclassified
See 1 more Smart Citation